2017
DOI: 10.5301/ejo.5000978
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Centered and Visual Quality Outcomes of Premium Cataract Surgery: A Systematic Review

Abstract: Studies are needed to thoroughly compare patient-reported outcomes with concomitant patient expectations. In light of the substantial patient costs for premium options, patients and their surgeons will benefit from a better understanding of which surgical options best meet patients' expectations and how those expectations can be impacted by premium versus monofocal-including monovision-options.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
91
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(95 citation statements)
references
References 89 publications
(193 reference statements)
1
91
1
2
Order By: Relevance
“…CS improved with time and achieved an age normal range of 3-12 months after surgery. Similar results were presented in the meta-analysis by Rosen et al [32] and in the review by Wang et al [33]. Thus, doubts remain as to which MIOL design would offer the best visual performance and patient satisfaction in patients with retinal disease.…”
Section: Cs and Miolssupporting
confidence: 72%
“…CS improved with time and achieved an age normal range of 3-12 months after surgery. Similar results were presented in the meta-analysis by Rosen et al [32] and in the review by Wang et al [33]. Thus, doubts remain as to which MIOL design would offer the best visual performance and patient satisfaction in patients with retinal disease.…”
Section: Cs and Miolssupporting
confidence: 72%
“…In contrast, patient dissatisfaction with the pseudophakic mini-monovision technique is mostly related to the refractive outcome, which can be corrected with spectacles or contact lenses and does not require additional surgery. A systematic review of research on quality outcomes revealed that patients with multifocal IOLs are more likely than patients with pseudophakic mini-monovision technique to undergo IOL exchange due to dissatisfaction with image quality [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] With recent developments in intraocular lens (IOL) and biometry technology, stand-alone cataract surgery now provides a substantial opportunity to increase optical independence and vision-related quality of life. 4 Given this, patient expectations have similarly increased. Despite often long-term ophthalmic care, glaucoma patients would appear to hold similar expectations of an improved range of vision following cataract surgery.…”
Section: Introductionmentioning
confidence: 99%